THE USE OF ANDROID-BASED SIMADU (POSYANDU INFORMATION SYSTEM) APPLICATION IN BEJI - Abd Rahman, La; Handiyani, Hanny; Rachmi, Shanti Farida; Friska, Friska; Ayu, Vergeina; Rizaldi, Fakhri M (Universitas Respati Yogyakarta, 2021)
Thriving technology, information, and communication drive mobile health development to induce changes in health service delivery. The Android-based SIMADU application is a substitute for the manual and conventional administration system. It encourages Posyandu cadres to use the android-based application, which is considered more productive, and thereby making Posyandu activities more efficient. This research is discussing the Android-based SIMADU application. Method used is a descriptive survey, carried out in Posyandu Flamboyan, Mawar, Cempaka, and Kenanga, all addressed in Kukusan Beji Depok West Java. Data collection techniques are observation and questionnaire distribution. The sample is 25 cadres from Posyandus in Kukusan Beji. The results is 78.1% of Posyandu cadres advocate the use of the SIMADU application. 68.8% of Posyandu cadres entail an engineer who can assist them to use the SIMADU application. The SIMADU application features are attested to be effective to elevate Posyandu cadres’ confidence by 71.9%. The conclusion, use of technology and information in Posyandu may breed a significant change in health service delivery. The SIMADU application can help Posyandu cadres in Posyandu activities, e.g., recording and documenting the data of families, pregnant women, babies, toddlers, and fertile couples. Keywords: Posyandu Information System Application; Android